Plasmid DNA partitioning and separation using poly(ethylene glycol)/poly(acrylate)/salt aqueous two-phase systems - Johansson, Hans-Olof; Matos, Tiago; Luz, Juliana S.; Feitosa, Eloi [UNESP]; Oliveira, Carla C.; Pessoa, Adalberto; Buelow, Leif; Tjerneld, Folke (Elsevier B.V., 2012)
Phase diagrams of poly(ethylene glycol)/polyacrylate/Na2SO4 systems have been investigated with respect to polymer size and pH. Plasmid DNA from Escherichia coil can depending on pH and polymer molecular weight be directed to a poly(ethylene glycol) or to a polyacrylate-rich phase in an aqueous two-phase system formed by these polymers. Bovine serum albumin (BSA) and E. coil homogenate proteins can be directed opposite to the plasmid partitioning in these systems. Two bioseparation processes have been developed where in the final step the pDNA is partitioned to a salt-rich phase giving a total process yield of 60-70%. In one of them the pDNA is partitioned between the polyacrylate and PEG-phases in order to remove proteins. In a more simplified process the plasmid is partitioned to a PEG-phase and back-extracted into a Na2SO4-rich phase. The novel polyacrylate/PEG system allows a strong change of the partitioning between the phases with relatively small changes in composition or pH. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Plasmid DNA; Partitioning; Aqueous two-phase systems; Polyethylene glycol; Polyacrylate